(9, 8) Single‐Walled Carbon Nanotube Enrichment via Aqueous Two‐Phase Separation and Their Thin‐Film Transistor Applications. (15th October 2015) - Wei, Li; Liu, Bilu; Wang, Xintian; Gui, Hui; Yuan, Yang; Zhai, Shengli; Ng, Andrew Keong; Zhou, Chongwu; Chen, Yuan
Abstract : One‐step simultaneous diameter and metallicity enrichment of semiconducting (9, 8) single‐walled carbon nanotubes is achieved by a new aqueous two‐phase separation method. The enriched nanotubes have a band gap of 0.88 eV and a narrow emission window at 1400 nm, showing excellent potential for application in electronic and optoelectronic devices.